(untitled) (Fractal: Journal of Psychology, 2009)
To speak about corporal subjectivity is to comply with an obvious redundancy: all subjectivity is enmeshed in a corporal experience which is a condition of existence. Hence, there is no such thing as a non-corporal subjectivity: there is no subjectivity beyond embodied experience. However, it remains important to address the issue of corporal subjectivity to deny a dualistic positivism that disembodies the subject; to deny some constructivism that, trying to escape the modern essentialist ideologies in which "biology is destiny", sometimes to the limit, dimensions of existence where the lived body assumes inescapable centrality. Grounded on a long ethnographic account of the experiences of blind people in Portugal, I propose to explore the terms through which the embodied experience of blindness is construable, both as a lived experience and as a projective account. In this I will seek to outline a perspective through which the cultural hegemonic representations about blindness can be addressed through Merleau-Ponty’s concept of "body-subject" ("corps-sujet").